Mechanism of Astrin in Head and Neck Squamous Cell Carcinoma: Astrin in Head and Neck Squamous Cell Carcinoma - Wang, Jian; Liu, Changjian; Wei, Minghui (Cellular and Molecular Biology, 2022)
Head and neck squamous cell carcinoma(HNSCC) is a malignant epidermal tumor that seriously threatens human life and health. The main factors affecting the death of patients are local recurrence and lymph node metastasis. Astrin antibody is the basic component of the mitotic spindle required for normal chromosome separation and later development. There are few domestic studies on the mechanism of Astrin in HNSCC. Based on this, this article is studying Astrin in HNSCC. The expression and function of Astrin, and analyze its correlation with clinical pathological parameters and prognosis of patients, and further explore the relevant mechanisms involved in the progression of Astrin in HNSCC. In this experiment, the real-time fluorescent quantitative polymerase chain reaction (PCR) method was used to detect the expression of the Astrin antibody in HNSCC cell lines A and B. Secondly, this article will focus on high metastatic HNSCC cells B. Divided into five groups (blank control group, overexpression positive group, overexpression negative control group, expression suppression positive group, expression suppression negative control group), using real-time fluorescent quantitative PCR technology to detect the expression of Astrin in each group, and then speculate the mechanism of Astrin in HNSCC. Experiments have shown that Astrin is expressed in A and B cells, but its expression in B is significantly higher than its expression in A, and the difference is statistically significant (P<0.001). This shows that the inhibition of Astrin expression has a significant anti-tumor effect and that Astrin plays an important role in the occurrence and development of tumors. It is expected to provide new ideas and reference basis for exploring new therapeutic strategies for targeted therapy of HNSCC.